Pengaruh Evaluasi Diagnostik dan Produk Terhadap Peningkatan Kaidah Kebahasaan dalam Penulisan Teks Deskripsi Siswa Kelas VII: Penelitian - Sa’datun Wafiroh; Ika Septiana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the results of diagnostic evaluation and product evaluation in learning linguistic rules in writing descriptive texts for 32 seventh grade students. Diagnostic evaluation was conducted to map students' initial abilities related to the use of adjectives, specific words, sensory words, and simple figures of speech in writing descriptive texts. Furthermore, product evaluation was used to assess students' abilities in applying these linguistic rules to the descriptive texts they wrote. The results of the study showed a significant increase in abilities after the learning was given. This was seen from the increase in the number of students in the good and very good categories, as well as the decrease in the number of students who needed guidance at the product evaluation stage. These findings indicate that learning linguistic rules in descriptive texts can effectively improve students' writing skills and have a positive impact on mastery of relevant linguistic elements.